Variable-length signatures for intrusion detection - Li, Zhuowei (2011)
Intrusion detection has become a basic infrastructure to guarantee the security of most internetworking applications. With more internetworking applications in the Internet nowadays, enormous volume of audit trails are produced for the analysis within intrusion detection. For this reason, it is critical to reduce the detection computation of intrusion detection to